Application of Deep Breathing Relaxation Techniques Accompanied by Mozart's Classical Music to Reduce Anxiety Disorders in Elderly Hypertensive Patients: Sambongpari Community Health Center, Tasikmalaya City - Ria Daniarti; Dudi Hartono; Peni Cahyati; Asep Riyana (International Journal Of Health Science, 2025)
One of the most common diseases suffered in Tasikmalaya City is hypertension, which is especially common in the Sambongpari Health Center service area. One of the psychological impacts on the elderly who have a history of hypertension is anxiety disorders that affect the quality of life. Deep breathing exercises and Mozart classical music therapy are two non-pharmacological methods that can be used to reduce anxiety. The purpose of this study was to determine the description of the application of deep breathing relaxation techniques accompanied by Mozart classical music in reducing anxiety in elderly hypertensive patients. Hypertension is a chronic condition known as a silent killer that can cause serious consequences including heart failure, stroke, and kidney disease without symptoms. Anxiety is a change in condition felt by a person that can cause fear and anxiety caused by internal and external threats. The study used a descriptive case study approach with two elderly subjects who had hypertension accompanied by anxiety disorders. The intervention was carried out for five days in the Sambongpari Health Center work area of ​​Tasikmalaya City. Measurement of anxiety scores before and after the intervention, observation, and interviews were used to collect data. Based on the results, the anxiety scores of both clients decreased after receiving regular deep breathing relaxation exercises while listening to Mozart classical music.  Based on the research results, elderly with a history of hypertension can effectively reduce their anxiety levels by combining deep breathing relaxation techniques with Mozart's classical music. This intervention is an effective non-pharmacological therapy option to reduce anxiety.